Exposure-Related Anxiety and Improving Patient Satisfaction with Medical Undergarments During Surgery: A Randomized Controlled Trial. (3rd August 2022) - Jacofsky, Marc C.; Auran, Richard L.; Williams, Alyse; Mauro, Susan; Sietsema, Debra
Abstract : Background: The standard of care for patients undergoing a surgical procedure is to have patients remove all clothing and don a hospital-provided gown. A growing number of patients have anxiety when exposing their bodies in a medical setting, which increases stress for those patients. Methods: This study prospectively enrolled patients at a single orthopaedic specialty hospital into 1 of 2 garment groups in a block-randomized design. Patients were asked to remove all clothing; 100 patients received the standard-of-care gown only, and 100 patients received the standard-of-care gown plus a single-use undergarment designed with retractable panels and a releasable waistband. Patients completed surveys evaluating their levels of anxiety with regard to exposing their bodies in a medical setting. Results: There were 181 subjects (91%) who completed the preoperative surveys and 166 subjects (83%) who completed the post-discharge surveys. Fifty-seven subjects (31%) reported being uncomfortable exposing their private, intimate parts in a medical setting, and 39 subjects (22%) reported experiencing stress and/or anxiety related to body exposure. Ninety-seven patients (54%) agreed or strongly agreed that protecting their personal modesty is important when undergoing a medical procedure. More patients in the undergarment group agreed or strongly agreed that the garments provided by the hospital met their expectation for privacy (80 patients [87%]), compared with the standard-of-care group (65 patients [73%]) (p = 0.025). Patients in the undergarment group (36 patients [39%]) were more likely than those in the standard-of-care group (16 patients [18%]) to strongly agree that they were satisfied with the hospital-provided garments (p = 0.028). When asked if the hospital-provided garments would influence their choice of hospital, patients in the undergarment group agreed or strongly agreed 3 times as often (19%) as the standard-of-care group (6.6%) (p = 0.06). Conclusions: Exposure-related stress and/or anxiety are experienced by a substantial percentage of surgical patients, and the majority consider protection of their personal modesty in a medical setting to be important. The use of medical undergarments to protect modesty significantly increased levels of patient satisfaction. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.